Critical reflection on the academic writing standard of first-year English second-language students in a South African university: academic writing standard - Maluleke, mzamani; Demana, Ndishunwani Vincent (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2024)
This paper provides a critical reflection on the academic writing ability of English second language students in a South African university. Acquiring proficiency in academic writing is one of the essential skills that students at the tertiary level are expected to master. One challenge that has emerged after the outbreak of Covid-19 is that universities in restructuring their curriculum have not given adequate time to interact with beginning students to provide writing instructions to help them meet the standard expected; this challenge motivated the study. A qualitative research, method was used and data was collected from a selection of first-year students, registered in the first semester, for English which is a compulsory Communication Skills course. Participants were given a narrative essay and all scripts were marked and rated by two experienced lecturers, using a rubric. The findings indicated that students encounter numerous challenges in writing a coherent academic essay, as they have low proficiency in English which is the medium of instruction.